2018
DOI: 10.1017/s1041610218001345
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in balance and mobility identify delirium in patients with comorbid dementia

Abstract: Diagnosing delirium superimposed on dementia (DSD) remains challenging because of a lack of specific tools, though motor dysfunction in delirium has been relatively under-explored. This study aimed to use dysfunction in balance and mobility (with the Hierarchical Assessment of Balance And Mobility: HABAM) to identify DSD. This is a cross-sectional multicenter study, recruiting consecutive patients ≥70 years admitted to five acute or rehabilitation hospitals in Ireland, Italy, Portugal, and Switzerland. Deliriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…A novelty in this study was the documentation of the decline of full abilities, which reached 50-90%. Although evidence for activity (Yang et al, 2008), mobility and balance (Gual et al, 2019), as well as nutritional status and nutrients (Sanford and Flaherty, 2014) is vague on regular floors, this study confirmed gait and balance disturbances as well as nutritional aspects. Regarding the former, we have to assume that delirium caused gait and balance disturbances, and for latter, the energy and nutrient requirement, as well as parenteral nutrition and additional calories were increased.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…A novelty in this study was the documentation of the decline of full abilities, which reached 50-90%. Although evidence for activity (Yang et al, 2008), mobility and balance (Gual et al, 2019), as well as nutritional status and nutrients (Sanford and Flaherty, 2014) is vague on regular floors, this study confirmed gait and balance disturbances as well as nutritional aspects. Regarding the former, we have to assume that delirium caused gait and balance disturbances, and for latter, the energy and nutrient requirement, as well as parenteral nutrition and additional calories were increased.…”
supporting
confidence: 67%
“…Surprisingly, the literature on functional status in the delirious is rare and studied regular floors rather than the intensive care setting. As summarized in the Introduction, there is vague evidence for activity (Yang et al, 2008), mobility and balance in delirium superimposed on dementia (Gual et al, 2019), and nutritional status and nutrients in delirium contribution (Sanford and Flaherty, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, when analyzing motor function, impairments of worse motor function can be identified in patients with delirium in comparison with those without delirium, independently of the presence of underlying dementia [67]. These features have been used to improve the diagnosis of delirium superimposed on dementia (DSD), using only motor tools like the Tinetti scale or the Hierarchical Assessment of Balance and Mobility (HABAM) [35,67].…”
Section: (A) Disorders In Physical Function As Risk Factors For Deliriummentioning
confidence: 99%